Can Thai Students Survive without English Teachers? a Case Study of Primary School Students in Thailand - Dueraman, Bayatee; Tunsakul, Kanasin; ., . (International Journal of Engineering and Technology, 2018)
Particular interests in English language teaching practices have been given much attention recently. This study attempts to examine whether trained English majors can help teach English to students in a primary school where there is short of English teachers. Two English instructors, twenty English majors and ninety-four students participated in the study. Theoretical and practical training sessions were organized for twenty English majors before they start teaching the students.  English lesson plans were designed relative to four major content areas found in the standardized national English test include vocabulary, reading, conversation, and public signs were used as a guideline for both training and teaching sessions. Pre and post-tests were administered to primary school students before and after the teaching intervention accordingly. Data collected through participant observations were also used to support data collected from the interviews and tests. Results show that our trained English majors could help improve the students’ English language proficiency in spite the unavailability of qualified English teachers at their school. Findings offer some insights on possible alternatives to teaching English to primary school students who face similar problems.